A new species of Hemiphyllodactylus (Squamata: Gekkonidae) from Tuyen Quang Province, Vietnam - Do, Quyen Hanh; Pham, Cuong The; Phan, Tien Quang; Le, Minh Duc; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2020)
A new species of the gekkonid genus Hemiphyllodactylus is described from limestone karst forest of Tuyen Quang Province, northern Vietnam based on morphological differences and molecular divergence. Hemiphyllodactylus nahangensis sp. nov. is distinguished from the remaining congeners by having the unique combination of the following characters: a bisexual taxon; SVL of adults 41.4–43.6 mm; dorsal scale rows 18–23; ventral scale rows 9–13; chin scales bordering mental and first infralabial distinctly enlarged; 22–24 pore-bearing femoral and precloacal scales, in a continuous row, absent in females; digital lamella formula 3-4-5-4 (forefoot) and 4-5-5-5 (hindfoot); cloacal spur single, present in both sexes; dark lateral head stripe indistinct; postsacral mark cream and bearing anteriorly projecting arms. In phylogenetic analyses, the new species is placed in a clade that includes H. dushanensis, H. hongkongensis, H. huishuiensis, H. ngocsonensis and H. zugi. In terms of pairwise genetic distance, the new species is at least 5.9%–6.6% divergent from other congeners based on a fragment of the mitochondrial gene ND2.